Designing an Online Learning Environment for New Elementary Science Teachers: Supports for Learning to Teach - Davis, Elizabeth A.; Smithey, Julie; Petish, Debra (Proceedings of the 6th International Conference on Learning Sciences, 2004)
Elementary teachers have a tremendous impact on their students' future learning. Yet because of the high demands put on them, elementary teachers often demonstrate weak subject matter knowledge in science (Anderson & Mitchener, 1994) and lack confidence in teaching science (Cochran & Jones, 1998). Likewise, prospective and new science teachers face many challenges, including that they may hold little pedagogical content knowledge (van Driel, Verloop, & de Vos, 1998). Thus new elementary science teachers need support, and it is critical to understand how best to provide that support. In our extended white paper (available at http://www.umich.edu/~betsyd) we present a design narrative describing CASES (Curriculum Access System for Elementary Science; available at http://cases.soe.umich.edu). CASES, a technology-mediated learning environment supporting new elementary science teachers as they learn to teach inquiry-oriented science more effectively, incorporates inquiry-oriented unit plans that are intended to be educative for teachers, as well as a personal online journal and an online teacher community discussion space. CASES is grounded in three main design principles that we present here.